STRENGTHENING RESPECT CHARACTER OF PRIMARY SCHOOL STUDENTS THROUGH TRADITIONAL GAME "JARANAN" - Amaliyah Ulfah (CAKRAWALA DINI: JURNAL PENDIDIKAN ANAK USIA DINI, 2018)
Abstract:. Indonesia is widely known as a multicultural nation which upholds respect and manners. Respect character can be interpreted as a good attitude for others. However, now the phenomenon of gradually decreasing of children's respect for friends and elder people including teachers has been worrying. Therefore, it is necessary to strengthen students’ respect character, and it should be taught as early as possible. One of the efforts that can be done to strengthen the children’s respect character is by integraing traditional games in primary school learning. The game "Jaranan" which comes from Central Java seems to be appropriate to teach children importance togetherness and respect for elder people.Keyword: local wisdom, respect character, primary school students Abstrak: Indonesia dikenal luas sebagai negara multikultural yang menjunjung tinggi rasa hormat dan sopan santun. Karakter respek dapat diartikan sebagai sikap yang baik untuk orang lain. Namun, sekarang fenomena penurunan rasa hormat anak-anak secara bertahap untuk teman dan orang tua termasuk guru telah mengkhawatirkan. Oleh karena itu, perlu untuk memperkuat karakter penghormatan siswa, dan itu harus diajarkan sedini mungkin. Salah satu upaya yang dapat dilakukan untuk memperkuat karakter rasa hormat anak adalah dengan mengintegrasikan permainan tradisional dalam pembelajaran sekolah dasar. Permainan "Jaranan" yang berasal dari Jawa Tengah tampaknya tepat untuk mengajarkan anak-anak pentingnya kebersamaan dan menghormati orang tua.Kata Kunci: kearifan lokal, karakter menghormati, siswa SD